Credit Risk Analytic Using Logistic Regression and Decision Trees - Manoj Kumar Srivastava; Namita Srivastava; Sandeep (International Journal of Mathematics And its Applications, 2018)
This paper examines current practices, problems, and prospects of data and image classification. Data and Image classification is a complex process that may be affected by many factors. The emphasis is placed on the summarization of major advanced classification approaches and the techniques used for improving classification accuracy. In addition, some important issues affecting classification performance are discussed. This literature review suggests that designing a suitable data and image processing procedure is a prerequisite for a successful classification of remotely sensed data into a thematic map. Effective use of multiple features of remotely sensed data and the selection of a suitable classification method are especially significant for improving classification accuracy. Non parametric classifiers such as neural network, decision tree classifier, and knowledge based classification have increasingly become important approaches for multisource data classification. Integration of remote sensing, geographical information systems (GIS), and expert system emerges as a new research frontier. More research, however, is needed to identify and reduce uncertainties in the image-processing chain to improve classification accuracy.